A simple matrix to predict treatment success and long-term survival among patients undergoing pancreatectomy. Issue 2 (February 2019) - Fitzgerald, Timothy L.; Hunter, Lucas; Mosquera, Catalina; Jindal, Charulata; Biswas, Tithi; Zervos, Emmanuel; Efird, Jimmy T.
Abstract: Background: A more accurate measure of long-term survival among patients who have undergone a successful resection for pancreatic adenocarcinoma may be computed by accounting for time already survived during the initial treatment window. Methods: Patients diagnosed with pancreatic adenocarcinoma, from 2004 through 2013, were identified from the American College of Surgeons National Cancer Database (NCDB). A risk-stratification matrix was constructed including age, histopathologic factors and the use of adjuvant therapy, given successful treatment and survival at 3-month following diagnosis. Results: A total of 25, 897 patients (50% male, 53% >65 years of age) presented with stage I–III pancreatic cancer. The majority of patients had tumors >2 cm size (82%), grade I/II (65%), lymphatic invasion (LI) (66%), and negative margins (76%). A survival advantage for adjuvant therapy was observed among all patients, independent of their risk-profile. For example, a patient ≤65 years of age, with early stage cancer (size ≤2 cm, grade I/II, −ve LI, −ve margins) who received adjuvant therapy had a 62% probability of being alive beyond three years (95%CI = 59%–66%). In contrast, the survival probability decreased to 53% (95%CI = 59%–66%) without adjuvant therapy. Conclusions: These results provide surgeons and patients with more accurate information regarding long-term survival, as well as the benefit of opting for adjuvant therapy after successful pancreatic surgery.